Cornual pregnancy. A case report of unusual evolution with a single dose of methotrexate - Monzón Castillo, Eli Pedro (2020)
Cornual pregnancy is a rare entity associated with high morbidity and mortality. Diagnosis is challenging because the embryo usually appears on ultrasound as localized inside the uterus. Cornual pregnancy is more dangerous than other ectopic pregnancies, and cornual rupture may lead to severe maternal hemorrhage. It has the same risk factors as tubal pregnancy. Early diagnosis allows either medical treatment with methotrexate or conservative surgical treatments. We present a case of cornual pregnancy with unusual evolution to a single dose of methotrexate.